2013
DOI: 10.1614/ws-d-12-00128.1
|View full text |Cite
|
Sign up to set email alerts
|

Methiozolin Absorption and Translocation in Annual Bluegrass (Poa annua)

Abstract: Annual bluegrass is a problematic turfgrass weed. Methiozolin is a new, currently unregistered herbicide that selectively controls annual bluegrass in desirable turfgrasses. Studies were conducted to evaluate and compare annual bluegrass control from PRE-applied methiozolin as influenced by rate and soil type and from POST-applied methiozolin as influenced by rate, soil type, annual bluegrass growth stage, and treatment placement. Studies were also conducted to evaluate foliar and root absorption and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 32 publications
(59 reference statements)
3
28
0
Order By: Relevance
“…The K d values observed are consistent with other soil‐active herbicides (Table ). These data corroborate previous researchers who reported that methiozolin has soil activity for control of annual bluegrass …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The K d values observed are consistent with other soil‐active herbicides (Table ). These data corroborate previous researchers who reported that methiozolin has soil activity for control of annual bluegrass …”
Section: Resultssupporting
confidence: 93%
“…Overall, results indicate that ∼24% of applied methiozolin remains available for root uptake, but binds sufficiently to soil so as to resist leaching displacement. Thus, these studies indicate that methiozolin is available in soil for herbicidal activity, which has been observed in selective placement and field studies …”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations